1989
DOI: 10.1073/pnas.86.17.6508
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteolytic activation of factor VIII-von Willebrand factor complex by thrombin.

Abstract: Blood coagulation factor VIII (fVI) is a plasma protein that is decreased or absent in hemophilia A. It is isolated as a mixture of heterodimers that contain a variably sized heavy chain and a common light chain. Thrombin catalyzes the activation of fVIII in a reaction that is associated with cleavages in both types of chain. We isolated a serine protease from Bothropsjararacussu snake venom that catalyzes thrombin-like heavy-chain cleavage but not light-chain cleavage in porcine fVIII as judged by NaDodSO4/PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
48
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 31 publications
0
48
1
Order By: Relevance
“…Cleavage at Arg 1689 is responsible for the dissociation of fVIII from vWf (11-13), which is a requisite step during fVIII activation because fVIII bound to vWf cannot bind to phospholipid membranes (14, 15). However, in the absence of vWf, cleavage at Arg 1689 is not required to produce a fVIIIa molecule with substantial activity (12,13,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cleavage at Arg 1689 is responsible for the dissociation of fVIII from vWf (11-13), which is a requisite step during fVIII activation because fVIII bound to vWf cannot bind to phospholipid membranes (14, 15). However, in the absence of vWf, cleavage at Arg 1689 is not required to produce a fVIIIa molecule with substantial activity (12,13,16).…”
mentioning
confidence: 99%
“…Cleavage at Arg 1689 is responsible for the dissociation of fVIII from vWf (11-13), which is a requisite step during fVIII activation because fVIII bound to vWf cannot bind to phospholipid membranes (14, 15). However, in the absence of vWf, cleavage at Arg 1689 is not required to produce a fVIIIa molecule with substantial activity (12,13,16).At the plasma concentration of fVIII (ϳ1 nM) at physiological pH, human fVIIIa activity spontaneously decays to undetectable levels with a half-life of 2 min at 23°C (17-19) as a result of A2 subunit dissociation (4,5,20). A2 subunit dissociation is a reversible process, and active, heterotrimeric fVIIIa can be reconstituted using sufficiently high concentrations of purified A2 subunit and A1/A3-C1-C2 dimer (5).…”
mentioning
confidence: 99%
“…Activated fVIII (fVIIIa) is a heterodimer of 50-, 43-, and 73-kDa subunits, all of which are required for procoagulant activity (12). Cleavage of the LCh at Arg 1689 , which releases the acidic region (fVIII residues 1649 -1689), is responsible for dissociation of fVIIIa from vWf (8,13). The importance of the LCh acidic region for fVIII binding to vWf was suggested by the observations that several anti-acidic region monoclonal antibodies (mAbs) with epitopes within residues 1670 -1689 (14 -17) inhibit fVIII binding to vWf, as does complete deletion of the acidic region (18).…”
mentioning
confidence: 99%
“…A central question is whether light chain cleavage is essential only for the dissociation ofFactor VIII from vWf, or ifit is an intrinsic requirement for FVIII activity. This issue has been studied by Hill-Eubanks, Parker, and Lollar, using a snake venom protease that generates a thrombin-like cleavage ofthe porcine Factor VIII heavy chain, but that does not cleave the light chain (16). These investigators showed that porcine Factor VIII procoagulant activity can be generated by heavy chain cleavage alone if vWf is removed.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with that observation, porcine vWf inhibited the VIII:C function of venom enzyme-activated porcine Factor VIII, but it had no effect on thrombin-activated Factor VIII. For this reason, Hill-Eubanks et al suggested that the essential role of light chain cleavage is the dissociation of the vWf/Factor VIII complexes (16).…”
Section: Introductionmentioning
confidence: 99%